Quantification: The View From Natural Language Generation - Carstensen, Kai-Uwe (Frontiers in Artificial Intelligence, 2021)
Quantification is one of the central topics in language and computation, and the interplay of collectivity, distributivity, cumulativity and plurality is at the heart of the semantics of quantification expressions. However, its aspects are usually discussed piecemeal, distributed, and from an interpretative perspective with selected linguistic examples, often blurring the overall picture. In this paper, quantification phenomena are investigated from the perspective of natural language generation. Starting with a small-scale, but realistic scenario, the necessary steps towards generating quantifiers for a perceived situation are explained. Together with the automatically generated descriptions of the scenario, the observations made are shown to present new insights into the interplay, and the semantics of quantification expressions and plurals, in general. The results highlight the importance of taking different points of view in the field of language and computation.